The role of the external auditor in activating the internal control system And its implications for achieving transparency of financial reporting : Field study in a sample of audit offices operating in Erbil - Kurdistan Region Iraq - Mahmood, Mohammed Obaid; Mehdi AL-Insari, Abdulrasul Salih (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The aim of this study is to know the role of the external auditor on activating the internal control system and reflecting that on the achievement offinancial reporting transparency. Recently, Economic entities are facing various challenges due to the large and rapid changes in the business environmentas well as,the conflicts of interest and the multiplicity of viewsaffected by the unit's activities. Because of, the increase in cases of errors and irregularities, it was seen necessary to activate the internal control system through the role that could be played by the external auditor to adapt and communicate with this dynamic environment, and achieve a high level of transparency in financial reporting. The study also examinesthe relationship and the effect of the internal control system as an effective variable between the external auditor and the achievement offinancial reporting transparency which was represented as (The necessary professional care, internal control and disclosure level), to indicate the extent to which the transparency of financial reporting contributes to raising the performance of these factors in the audit firms operating in Arbil. To achieve these tests, four main hypotheses have been formulated and which are branched as twelve sub hypothesis directed to test those variables and find the relationships between them. In order to achieve this, exploratory approach has been used and a questionnaire has been distributed to the external auditors working in the audit firms in Erbil. The study has found several important conclusions in the theoretical and field study. The most important was that the activation of the internal control system by the external auditor contributes to achieving a high level of transparency in financial reporting. In addition, the internal control system is considered as a partial intermediary between the external auditor and the achievement of the financial reporting transparency. The study has also concluded several recommendations the most important was the in-depth study of the internal control system and absorbing the utmost importance for the promotion and strengthening of its components in order to ensure the transparency of the information represented in the financial statements.